Polycarbonate compositions and polycarbonate materials, and methods of making and using the same
Patent Information
- Application Number
- CN202210891459.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-07-27
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2042-07-27
AI Technical Summary
[0003]本发明的目的是为了克服现有技术存在的PC/ABS塑料合金延展性差,导致挤出凹型管材等易变形或吹塑加工易破裂的问题,提供一种聚碳酸酯组合物和聚碳酸酯材料及其制备方法和应用,该聚碳酸酯组合物延展性高、耐化学性优异
[0011]通过上述技术方案,本发明提供的聚碳酸酯组合物中,加入聚对苯二甲酸乙二醇酯,能够改善PC/ABS的延展性,该组合物制备的聚碳酸酯材料具有高延展性,高耐化学性和优异的加工稳定性,特别适用于吹塑加工和用于制备挤出凹型管材。
Smart Images

Figure BDA0003767701380000101 
Figure BDA0003767701380000102
Abstract
Description
Technical Field
[0001] This invention relates to the field of polycarbonate materials technology, specifically to a polycarbonate composition and polycarbonate material, its preparation method and application. Background Technology
[0002] Traditional PC / ABS plastic alloys are prone to cracking and difficult to mold in thin-wall blow molding due to the influence of ABS. They are also prone to deformation during the extrusion of concave tubes. It is necessary to improve the ductility of PC / ABS. Existing improvement methods include increasing the rubber content in ABS and reducing the content of styrene and acrylonitrile. However, this technical solution has the following drawbacks: it is easily affected by the equipment of the extrusion or blow molding plant. The butadiene, acrylonitrile, and styrene contents that need to be adjusted to meet the normal production needs of different equipment are different, which will increase the amount of research and development work. Summary of the Invention
[0003] The purpose of this invention is to overcome the problem of poor ductility of PC / ABS plastic alloys in the prior art, which leads to easy deformation of extruded concave tubes or easy breakage during blow molding. This invention provides a polycarbonate composition and polycarbonate material, as well as their preparation method and application. The polycarbonate composition has high ductility and excellent chemical resistance.
[0004] To achieve the above objectives, a first aspect of the present invention provides a polycarbonate composition comprising:
[0005] Polycarbonate (PC) 40-60 parts by weight, acrylonitrile-butadiene-styrene copolymer (ABS) 20-40 parts by weight, styrene-acrylonitrile copolymer (SAN) 5-15 parts by weight, polyethylene terephthalate (PET) 5-10 parts by weight, antioxidant 0.1-0.5 parts by weight, mold release agent 0.1-0.5 parts by weight, compatibilizer 0-8 parts by weight, toughening agent 0-3 parts by weight;
[0006] The intrinsic viscosity of the polyethylene terephthalate is 0.78-0.85 dL / g.
[0007] A second aspect of the present invention provides a polycarbonate material formed by heating, melting and extruding the composition described in the present invention into granules.
[0008] A third aspect of the present invention provides a method for preparing a polycarbonate material, the method comprising:
[0009] The composition of the present invention is mixed in proportion, and the mixed material is put into a twin-screw extruder for extrusion granulation. The screw length-to-diameter ratio is 32-36:1, and the temperature of each screw section is 200-260℃.
[0010] The fourth aspect of the present invention provides an application of the polycarbonate material described herein in extruded concave tubes and thin-walled blow molding.
[0011] Through the above technical solution, the polycarbonate composition provided by the present invention, by adding polyethylene terephthalate, can improve the ductility of PC / ABS. The polycarbonate material prepared by this composition has high ductility, high chemical resistance and excellent processing stability, and is particularly suitable for blow molding and for preparing extruded concave tubes.
[0012] As a preferred embodiment of the present invention, the addition of epoxy and / or acrylic compatibilizers can further improve the ductility of polycarbonate materials. In particular, the addition of a multi-component copolymer of glycidyl methacrylate (GMA) and methyl acrylate (MA) can simultaneously achieve the graft compatibility between PC, ABS, and PET, further improving the ductility of polycarbonate materials. Detailed Implementation
[0013] The endpoints and any values of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of the various ranges, the endpoint values of the various ranges and individual point values, and individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.
[0014] A first aspect of the present invention provides a polycarbonate composition comprising:
[0015] The composition includes 40-60 parts by weight of polycarbonate, 20-40 parts by weight of acrylonitrile-butadiene-styrene copolymer, 5-15 parts by weight of styrene-acrylonitrile copolymer, 5-10 parts by weight of polyethylene terephthalate, 0.1-0.5 parts by weight of antioxidant, 0.1-0.5 parts by weight of release agent, 0-8 parts by weight of compatibilizer, and 0-3 parts by weight of toughening agent; the intrinsic viscosity of the polyethylene terephthalate (PET) is 0.78-0.85 dL / g.
[0016] In this invention, the intrinsic viscosity test standard for PET is ASTM D4603, and the intrinsic viscosity of PET is tested at 30°C.
[0017] The polycarbonate composition provided by this invention incorporates polyethylene terephthalate, which improves the ductility of PC / ABS. The polycarbonate material prepared by this composition exhibits high ductility, high chemical resistance, and excellent processing stability.
[0018] In the polycarbonate composition of the present invention, a toughening agent may be optionally added or not added, and the toughening agent in the polycarbonate composition may be 0 parts, 0.5 parts, 1 part, 2 parts, or 3 parts by weight.
[0019] In the polycarbonate composition of the present invention, a compatibilizer may be added or not added, and the weight parts of the compatibilizer in the polycarbonate composition may be 0 parts, 0.5 parts, 1 part, 2 parts, 3 parts, 4 parts, 5 parts, 6 parts, 7 parts, or 8 parts.
[0020] According to a preferred embodiment of the present invention, the polycarbonate composition comprises: 40-60 parts by weight of polycarbonate (PC), 20-40 parts by weight of acrylonitrile-butadiene-styrene copolymer (ABS), 5-15 parts by weight of styrene-acrylonitrile copolymer (SAN), 5-10 parts by weight of polyethylene terephthalate (PET), 0.1-0.5 parts by weight of antioxidant, 0.1-0.5 parts by weight of release agent, 2-8 parts by weight of compatibilizer, and 1-3 parts by weight of toughening agent.
[0021] According to a preferred embodiment of the present invention, the polycarbonate has a melt index of 5-30 g / 10 min at 300°C and 1.2 kg load, preferably 10-20 g / 10 min; this is beneficial for improving the ductility, chemical resistance and processing stability of the polycarbonate material.
[0022] According to a preferred embodiment of the present invention, the polycarbonate has a weight-average molecular weight of 10,000-50,000 g / mol.
[0023] In this invention, the polycarbonate is commercially available, such as PC02-20 produced by Zhejiang Tie Dafeng Chemical Co., Ltd.
[0024] The polycarbonate composition provided by the present invention, by adding polyethylene terephthalate, can improve the ductility of PC / ABS. According to a preferred embodiment of the present invention, the weight-average molecular weight of the polyethylene terephthalate is 10,000-50,000 g / mol; this is beneficial to improving the ductility, chemical resistance and processing stability of polycarbonate materials.
[0025] In this invention, polyethylene terephthalate is commercially available, such as CB-602 from Shanghai Yuanfang Industrial Co., Ltd.
[0026] In this invention, the acrylonitrile-butadiene-styrene copolymer (ABS) has a high butadiene content, which can improve the elasticity of the material to a certain extent and is beneficial for extrusion and blow molding. According to a preferred embodiment of this invention, based on the total amount of the acrylonitrile-butadiene-styrene copolymer (ABS), the content of structural units from butadiene in the acrylonitrile-butadiene-styrene copolymer is 60wt%-75wt%, which is beneficial for improving the ductility of polycarbonate materials.
[0027] According to a preferred embodiment of the present invention, based on the total amount of the acrylonitrile-butadiene-styrene copolymer, the content of structural units from butadiene in the acrylonitrile-butadiene-styrene copolymer is 60wt%-75%, the content of structural units from acrylonitrile is 15wt%-30wt%, and the content of structural units from styrene is 10wt%-20wt%, which is beneficial to further improve the ductility of the polycarbonate material.
[0028] According to a preferred embodiment of the present invention, the acrylonitrile-butadiene-styrene copolymer has a melt index of 1-10 g / 10 min at 230°C and 3.8 kg load; this is beneficial for improving the ductility, chemical resistance and processing stability of polycarbonate materials.
[0029] According to a preferred embodiment of the present invention, the acrylonitrile-butadiene-styrene copolymer has a melt index of 0.5-10 g / 10 min at 220°C and 10 kg load.
[0030] In this invention, the acrylonitrile-butadiene-styrene copolymer is commercially available, for example, WD-132 produced by Shandong Wanda Chemical Co., Ltd.
[0031] According to a preferred embodiment of the present invention, based on the total amount of the styrene-acrylonitrile copolymer (SAN), the content of structural units from acrylonitrile in the styrene-acrylonitrile copolymer is 30wt%-60wt%, and the content of structural units from styrene is 40wt%-70wt%, which is beneficial to improving the ductility of the polycarbonate material. It is commercially available, for example, NF2200 produced by Formosa Plastics (Ningbo) Co., Ltd.
[0032] In this invention, the compatibilizer is used to improve the compatibility between the three components PC, ABS, and PET, enabling the three components to graft and become compatible with each other. It also reduces the active reactive groups at the ends of PC and ABS, which is beneficial to improving the ductility, chemical resistance, and processing stability of polycarbonate materials. According to a preferred embodiment of the invention, the compatibilizer is selected from epoxy and / or acrylic compatibilizers, and preferably, the content of active functional groups in the compatibilizer is 13wt%-17wt%.
[0033] According to a preferred embodiment of the present invention, the compatibilizer is a polymer copolymerized from glycidyl methacrylate and methyl acrylate; preferably, based on the total amount of the compatibilizer, the content of structural units from glycidyl methacrylate is 50-75 wt%, and the content of structural units from methyl acrylate is 25-50 wt%; this is beneficial for improving the ductility, chemical resistance, and processing stability of polycarbonate materials. It is commercially available, for example, Jia Yi Rong SOG-02.
[0034] In this invention, the antioxidant can be used to improve the chemical resistance of polycarbonate materials. According to a preferred embodiment of the invention, the antioxidant is octadecyl β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate and / or tris(2,4-di-tert-butylphenyl) phosphite, preferably a complex of octadecyl β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate and tris(2,4-di-tert-butylphenyl) phosphite. More preferably, in the antioxidant, the mass ratio of octadecyl β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate to tris(2,4-di-tert-butylphenyl) phosphite is 1:0.2-5.
[0035] According to a preferred embodiment of the present invention, the release agent is selected from at least one of polyethylene wax, paraffin wax, ethylene bis-stearamide, and pentaerythritol bis-stearate.
[0036] In this invention, the addition of a toughening agent can improve the ductility and impact resistance of polycarbonate materials. According to a preferred embodiment of the invention, the toughening agent is selected from a terpolymer of methyl methacrylate, butadiene, and styrene. The toughening agent is commercially available, for example, M722 manufactured by Kaneka Corporation of Japan.
[0037] The polycarbonate composition provided by this invention includes components that can synergistically enhance each other to achieve the technical objectives of this invention. The composition comprises specific polycarbonate (PC), acrylonitrile-butadiene-styrene copolymer (ABS), styrene-acrylonitrile copolymer (SAN), and polyethylene terephthalate (PET). Within the aforementioned dosage range, using PET with an intrinsic viscosity of 0.78-0.85 dL / g improves the chemical resistance of the obtained polycarbonate material. Furthermore, the addition of PET resin may lead to a slight transesterification reaction with the polycarbonate, enhancing the material's stability, reducing the reactivity of the original PC / ABS alloy, improving the chemical resistance of the polycarbonate material, and enhancing its ductility and processing stability. This results in a polycarbonate material with high ductility, high chemical resistance, and excellent processing stability.
[0038] A second aspect of the present invention provides a polycarbonate material, which is obtained by melt blending the composition described in the present invention; the polycarbonate material described in the present invention has high ductility, high chemical resistance and excellent processing stability, and high notched impact strength.
[0039] A third aspect of the present invention provides a method for preparing the polycarbonate material described herein, the method comprising:
[0040] The components of the composition described in this invention are mixed, and the mixed material is fed into a twin-screw extruder for extrusion granulation. The screw length-to-diameter ratio is 32-36:1, and the temperature of each screw section is 200-260℃.
[0041] According to a preferred embodiment of the present invention, the temperature of the feeding section of the twin-screw extruder is 200-220°C, the temperature of the melting section is 250-260°C, the temperature of the homogenization section is 230-250°C, and the temperature of the die head is 220-240°C.
[0042] A fourth aspect of this invention provides the application of the polycarbonate material described herein in extruded concave tubes and thin-walled blow molding. The polycarbonate material described herein possesses high ductility, high chemical resistance, and excellent processing stability, making it particularly suitable for blow molding and the preparation of extruded concave tubes.
[0043] In the following examples, the testing indicators and methods for polycarbonate materials are as follows:
[0044] (1) Melt flow rate (MFR) is tested according to GB / T 3682 standard. The test conditions are 260℃ and 5kg load.
[0045] (2) Mechanical property testing: tensile strength and elongation at break: tested according to GB / T 1040 standard, test rate is 50mm / min; notched impact strength (cantilever beam): tested according to ISO180 standard.
[0046] (3) Chemical resistance test: Immerse the finished part in glacial acetic acid at 25°C for 2 minutes. After taking it out, wash it with water and air dry it naturally. Observe the surface condition. The degree of white frost on the surface is related to chemical resistance. The worse the chemical resistance, the more white frost. If the internal stress is too large, cracks will appear. The chemical resistance is determined by the number of "+". The more "+", the worse the chemical resistance.
[0047] (4) Thermal stability: The weight loss test shall be carried out in accordance with GB / T 2951.7. The weight loss shall be expressed as a percentage of the original weight. The greater the weight loss rate, the worse the thermal stability.
[0048] (5) Determination of blow molding effect: Set the temperature of each section of the blow molding machine to 250℃, the injection pressure to 70, and the blowing time to 10s, 15s, 20s, and 30s respectively. Record the blow molding effect by marking "☆" based on whether the material breaks after blowing for 10s, 15s, 20s, and 30s. The more "☆", the better the blow molding effect.
[0049] The present invention will be described in detail below through embodiments.
[0050] In the following embodiments, the raw materials include:
[0051] The PC used is PC02-20 produced by Zhejiang Tiedafeng Chemical Co., Ltd., which has a melt index of 20 g / 10 min at 300℃ and 1.2 kg load, and a weight-average molecular weight of 24000 g / mol.
[0052] The PET used is CB-602 from Shanghai Yuanfang Industrial Co., Ltd., with an intrinsic viscosity of 0.800±0.015 dL / g at 30℃ and a weight-average molecular weight of 25000 g / mol.
[0053] PET: Shanghai Yuanfang CB651S, intrinsic viscosity at 30℃: 0.755±0.015dL / g.
[0054] PET: Shanghai Yuanfang CB606, intrinsic viscosity at 30℃: 0.86 dL / g.
[0055] The ABS used is WD-132 produced by Shandong Wanda Chemical Co., Ltd. Based on the total amount of the acrylonitrile-butadiene-styrene copolymer, the content of structural units from butadiene in the acrylonitrile-butadiene-styrene copolymer is 65wt%, the content of structural units from acrylonitrile is 15wt%, and the content of structural units from styrene is 20wt%. The melt index of the acrylonitrile-butadiene-styrene copolymer at 230℃ and 3.8kg load is 4g / 10min.
[0056] The SAN resin used is NF2200 produced by Formosa Chemicals & Fibre (Ningbo) Co., Ltd. Based on the total amount of the styrene-acrylonitrile copolymer, the content of structural units from butadiene is 65wt%, and the melt index of the styrene-acrylonitrile copolymer at 220°C and 10kg load is 2.6g / 10min.
[0057] The antioxidants are commercially available antioxidants 1010, 168, and 1076.
[0058] The release agent is commercially available polyethylene wax.
[0059] Compatibilizer: RD880 produced by Ningbo Rongding Polymer Materials Co., Ltd., wherein the compatibilizer contains 65wt% structural units derived from glycidyl methacrylate and 35wt% structural units derived from methyl acrylate.
[0060] Compatibilizer: Jia Yi Rong SOG-02; GMA functional monomer grafted onto the main chain of ethylene elastomer, with a GMA functional group content of 15wt%.
[0061] The toughening agent is M722, manufactured by Kaneka Corporation of Japan.
[0062] In the following embodiments, the preparation method of polycarbonate material includes the following steps:
[0063] S1: Weigh out the raw materials such as PC, ABS, SAN resin, PET polyester, antioxidant, mold release agent, compatibilizer, and toughening agent according to the formula ratio and add them to the high-speed mixer and stir for 3 minutes;
[0064] S2: Then the mixed raw materials are put into a twin-screw extruder for extrusion granulation. The screw length-to-diameter ratio is 36:1, and the temperature of each section of the screw is between 200-260℃. The temperature of the feeding section of the twin-screw extruder is 200℃, the temperature of the melting section is 260℃, the temperature of the homogenization section is 240℃, and the temperature of the die head is 240℃.
[0065] The content of each component in Examples 1-6 is shown in Table 1. The test results are shown in Table 2.
[0066] Example 7
[0067] The difference from Example 1 is that no compatibilizer was added, and the content of each component is shown in Table 1 below. The test results are shown in Table 2.
[0068] Example 8
[0069] The difference from Example 1 is that the toughening agent Kanekachi M722 from Japan was replaced with M732, while the other conditions were the same as in Example 1. The test results are shown in Table 2.
[0070] Example 9
[0071] The difference from Example 1 is that the transparent Yuanfang CB602 was replaced with the opaque Yuanfang CB608S, wherein the intrinsic viscosity of CB608S is 0.800±0.015 dL / g, and the other conditions are the same as in Example 1. The test results are shown in Table 2.
[0072] Example 10
[0073] The difference from Example 1 is that the compatibilizer was replaced with Jia Yi Rong SOG-02, while the other conditions were the same as in Example 1. The test results are shown in Table 2.
[0074] Comparative Example 1
[0075] The method of Example 1 was followed, except that PET was not added. The contents of each component are shown in Table 1 below. The test results are shown in Table 3.
[0076] Comparative Example 2
[0077] The method of Example 1 was followed, except that the PET used was CB651S with an intrinsic viscosity of 0.755±0.015 dL / g, and the other conditions were the same as in Example 1. The test results are shown in Table 3.
[0078] Comparative Example 3
[0079] The method of Example 1 was followed, except that the PET used was CB606 with an intrinsic viscosity of 0.86 dL / g, and all other conditions were the same as in Example 1. The test results are shown in Table 3.
[0080] Table 1
[0081]
[0082] Table 2
[0083]
[0084] Table 3
[0085] Melt Flow Rate (MFR) 19.5 23.7 15.2 Tensile strength (MPa) 63.8 60.5 64.3 Elongation at break (%) 62.1 93.5 58.9 <![CDATA[Notched Impact Strength (kJ / m 2 )]]> 53.4 47.7 61.8 Chemical resistance ++++ ++++ ++++ blow molding effect ☆ ☆☆☆ ☆
[0086] As can be seen from Example 1 and Comparative Example 1, adding PET resin helps to improve the chemical resistance of the material, and may have a slight transesterification reaction with polycarbonate, which improves the stability of the material and weakens the reactivity of the original PC / ABS alloy; at the same time, it greatly improves the ductility of polycarbonate material, and even more so in blow molding processing.
[0087] As shown in Example 1 and Comparative Examples 2 and 3, the intrinsic viscosity of PET must be in the range of 0.78-0.85 dL / g to simultaneously improve the ductility and chemical resistance of polycarbonate materials, and the notched impact strength must exceed 60 kJ / m. 2 .
[0088] The preferred embodiments of the present invention have been described in detail above; however, the present invention is not limited thereto. Within the scope of the inventive concept, various simple modifications can be made to the technical solutions of the present invention, including combinations of various technical features in any other suitable manner. These simple modifications and combinations should also be considered as the content disclosed in the present invention and are all within the protection scope of the present invention.
Claims
1. A polycarbonate composition, characterized in that, The composition comprises: 40-60 parts by weight of polycarbonate, 20-40 parts by weight of acrylonitrile-butadiene-styrene copolymer, 5-15 parts by weight of styrene-acrylonitrile copolymer, 5-10 parts by weight of polyethylene terephthalate, 0.1-0.5 parts by weight of antioxidant, 0.1-0.5 parts by weight of mold release agent, 0-8 parts by weight of compatibilizer, and 0-3 parts by weight of toughening agent; The intrinsic viscosity of the polyethylene terephthalate is 0.78-0.85 dL / g. The intrinsic viscosity test standard for polyethylene terephthalate is ASTM D4603, and the intrinsic viscosity of polyethylene terephthalate is tested at 30℃. The polycarbonate has a melt index of 5-30 g / 10min and a weight-average molecular weight of 10,000-50,000 g / mol at 300°C and 1.2 kg load. Based on the total amount of the acrylonitrile-butadiene-styrene copolymer, the content of structural units from butadiene in the acrylonitrile-butadiene-styrene copolymer is 60wt%-75wt%, and the melt index of the acrylonitrile-butadiene-styrene copolymer at 230℃ and 3.8kg load is 1-10g / 10min; Based on the total amount of the styrene-acrylonitrile copolymer, the content of structural units from acrylonitrile in the styrene-acrylonitrile copolymer is 30wt%-60wt%, and the content of structural units from styrene is 40wt%-70wt%; the melt index of the styrene-acrylonitrile copolymer at 220℃ and 10kg load is 0.2-9g / 10min; The weight-average molecular weight of the polyethylene terephthalate is 10,000-50,000 g / mol.
2. The polycarbonate composition according to claim 1, wherein, The polycarbonate has a melt index of 10-20 g / 10min at 300℃ and 1.2kg load; And / or, the melt index of the acrylonitrile-butadiene-styrene copolymer at 220°C and 10 kg load is 0.5-10 g / 10 min; And / or, based on the total amount of the acrylonitrile-butadiene-styrene copolymer, the content of structural units from butadiene in the acrylonitrile-butadiene-styrene copolymer is 60wt%-75%, the content of structural units from acrylonitrile is 15wt%-30wt%, and the content of structural units from styrene is 10wt%-20wt%.
3. The polycarbonate composition according to claim 1 or 2, wherein, The compatibilizer is selected from epoxy and / or acrylic compatibilizers.
4. The polycarbonate composition according to claim 1 or 2, wherein, The compatibilizer is a polymer composed of glycidyl methacrylate and methyl acrylate as a multi-component copolymer.
5. The polycarbonate composition according to claim 4, wherein, Based on the total amount of the compatibilizer, the compatibilizer contains 50-75 wt% structural units derived from glycidyl methacrylate and 25-50 wt% structural units derived from methyl acrylate.
6. The polycarbonate composition according to claim 1 or 2, wherein, The antioxidant is β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate n-octadecyl alcohol ester and / or tris(2,4-di-tert-butylphenyl) phosphite; And / or, the release agent is selected from at least one of polyethylene wax, paraffin wax, ethylene bis-stearamide, and pentaerythritol distearate.
7. The polycarbonate composition according to claim 1 or 2, wherein, The antioxidant is a complex of β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate n-octadecyl alcohol ester and tris(2,4-di-tert-butylphenyl) phosphite; the mass ratio of β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate n-octadecyl alcohol ester to tris(2,4-di-tert-butylphenyl) phosphite is 1:0.2-5.
8. The polycarbonate composition according to claim 1 or 2, wherein, The toughening agent is selected from a terpolymer of methyl methacrylate, butadiene, and styrene.
9. A polycarbonate material, characterized in that, The polycarbonate material is obtained by melt blending of the composition according to any one of claims 1-8.
10. A method for preparing a polycarbonate material, characterized in that, The method includes: Mix the components of the composition according to any one of claims 1-8, and put the mixed material into a twin-screw extruder for extrusion granulation, wherein the screw length-to-diameter ratio is 32-36:1 and the temperature of each screw section is 200-260℃.
11. The preparation method according to claim 10, wherein, The twin-screw extruder has a feeding section temperature of 200-220℃, a melting section temperature of 250-260℃, a homogenization section temperature of 230-250℃, and a die head temperature of 220-240℃.
12. The application of the polycarbonate material according to claim 9 in extruded concave tubes and thin-walled blow molding.
Citation Information
Patent Citations
Flame retardant PC / PET composite material and preparation method thereof
CN101570628A
Polycarbonate / polyethylene glycol terephthalate resin composite and preparation method
CN101812223A